2003
DOI: 10.1021/bi020508+
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Energetics of the Binding between Barley α-Amylase/Subtilisin Inhibitor and Barley α-Amylase 2 Analyzed by Surface Plasmon Resonance and Isothermal Titration Calorimetry

Abstract: The kinetics and energetics of the binding between barley alpha-amylase/subtilisin inhibitor (BASI) or BASI mutants and barley alpha-amylase 2 (AMY2) were determined using surface plasmon resonance and isothermal titration calorimetry (ITC). Binding kinetics were in accordance with a 1:1 binding model. At pH 5.5, [Ca(2+)] = 5 mM, and 25 degrees C, the k(on) and k(off) values were 8.3 x 10(+4) M(-1) s(-1) and 26.0 x 10(-4) s(-1), respectively, corresponding to a K(D) of 31 nM. K(D) was dependent on pH, and whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…The BASI-AMY2 complex has been well described using site-directed mutagenesis, crystallography, surface plasmon resonance, and activity inhibition analyses (Vallée et al 1998;Rodenburg et al 2000;Nielsen et al 2003;Bønsager et al 2005) and found to have high stability, sub-nanomolar affinity; specific residues were assigned functional roles both in enzyme and inhibitor for the complex formation. Analysis of the LDI-limit dextrinase complex is just initiated thanks to breakthroughs with successful heterologous production of both LDI and limit dextrinase (M. VesterChristensen et al, manuscript in preparation) and data now emerge showing sub-nanomolar affinity also for this complex (J.M.…”
Section: New Roles and Diversity Of α-Glucan-active Enzymes In Biologmentioning
confidence: 99%
“…The BASI-AMY2 complex has been well described using site-directed mutagenesis, crystallography, surface plasmon resonance, and activity inhibition analyses (Vallée et al 1998;Rodenburg et al 2000;Nielsen et al 2003;Bønsager et al 2005) and found to have high stability, sub-nanomolar affinity; specific residues were assigned functional roles both in enzyme and inhibitor for the complex formation. Analysis of the LDI-limit dextrinase complex is just initiated thanks to breakthroughs with successful heterologous production of both LDI and limit dextrinase (M. VesterChristensen et al, manuscript in preparation) and data now emerge showing sub-nanomolar affinity also for this complex (J.M.…”
Section: New Roles and Diversity Of α-Glucan-active Enzymes In Biologmentioning
confidence: 99%
“…The K m of savinase for azoalbumin was 14 mg ϫ ml Ϫ1 as determined from the initial hydrolysis rates at seven substrate concentrations (0.5-12.5 mg ϫ ml Ϫ1 ). Surface Plasmon Resonance-Binding kinetics of BASI and either AMY2 or savinase was determined by using a BIAcore 3000 (Biosensor, Amersham Biosciences) (4,8). The sensor chips were charged by 300 -1000 response units of either biotinylated AMY2 (streptavidin-sensor chips), BASI, or savinase bound by using the amine coupling procedure (CM5 sensor chips) (8).…”
Section: Methodsmentioning
confidence: 99%
“…The double-headed barley ␣-amylase/subtilisin inhibitor (BASI) 1 of the Kunitz soybean trypsin inhibitor family acts on proteases of the subtilisin family and the endogenous high pI ␣-amylase (AMY2) but has no effect on the minor isozyme AMY1 that shares 80% sequence identity with AMY2 (1)(2)(3)(4)(5)(6)(7)(8). Under favorable conditions, BASI inhibits the AMY2-catalyzed hydrolysis of starch with a K i ϳ0.1 nM (2,4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The complex formation of AMY2 and BASI was described using surface plasmon resonance analysis which also facilitated studies of the effect of calcium on the stability of the AMY2 BASI complex. 24,25) While increasing [Ca 2+ ] from the low µM range to 20 mM evidently stabilised the complex by an order of magnitude, the dependence of the stability on pH suggested that a group in BASI of pKa around 6 participates in the binding to AMY2. The three dimensional structure of the AMY2 BASI pointed to Glu168 as an obvious candidate, since this residue through hydrogen bonds with the molecules in the water shell around Ca503 was indirectly in contact with the enzyme.…”
Section: Reactions Involving α-Amylases α-Amylase Inhibitors and Thimentioning
confidence: 99%